Given f(x)=3x+1, g(x)=x+2:

(1) The inverse of f(x) can be found by switching "x" and "y" and then solving for y.

y=3x+1

x=3y+1

3y=x-1

`y=(x-1)/3`

**So `f^(-1)(x)=(x-1)/3` **

** Note that in f(x) you multiply the input by 3 and then add 1 to the result. In the inverse, you subtract...

## Unlock

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

Given f(x)=3x+1, g(x)=x+2:

(1) The inverse of f(x) can be found by switching "x" and "y" and then solving for y.

y=3x+1

x=3y+1

3y=x-1

`y=(x-1)/3`

**So `f^(-1)(x)=(x-1)/3` **

** Note that in f(x) you multiply the input by 3 and then add 1 to the result. In the inverse, you subtract 1 from the input , then divide by 3. You perform the inverse operations in the reverse order.

(2) The inverse of g(x) is found in a similar manner:

y=x+2

x=y+2

y=x-2

**So `g^(-1)(x)=x-2` **

(3)Find (fg)(x):

This is simply the product f(x)g(x)

`(fg)(x)=(3x+1)(x+2)=3x^2+7x+2`